The United States and the Gulf shifting pressures, strategies and alignments - Hook, Steven W. 1959-; Niblock, Tim (Gulf Research Center book series, 2015)
The Gulf region's relations with the outside world are changing radically. The Gulf's major trading partners are now no longer predominantly Western. China, in particular, now has a significant stake and highly critical interests in the region. The United States still dominates the security field, yet its Gulf allies have come to doubt the strength of US commitment. Meanwhile the Arab monarchies of the Gulf are struggling to cope with multiple divisions, problems and threats: the radical forces of change unleashed by the Arab Spring, the rising power of ISIS, and the destabilising impact of their unsettled relations with Iran. This book examines the range of security issues which this situation has given rise to: the nature and scope of US power, and the likely directions of future policy; the options open to Asian powers with interests in the region; the concerns, strategies and dynamics of the regional states; and the feasibility of European states assuming a security role in the region.